Reconstitution of beta-adrenergic receptors in lipid vesicles: affinity chromatography-purified receptors confer catecholamine responsiveness on a heterologous adenylate cyclase system. - Cerione, R A (1983)
The binding function of purified receptors can be assessed with radioligands, but the interaction of receptors with their biochemical effectors has not been amenable to direct study. Toward this end, procedures have been developed for directly demonstrating functionality of purified beta-adrenergic receptor preparations. Digitonin-solubilized beta-adrenergic receptors from frog erythrocytes or rat lung were purified approximately equal to 100- to 5,000-fold by affinity chromatography and inserted into a mixture of frog erythrocyte lipids and dimyristoyl phosphatidylcholine in the presence of octyl glucoside. Reconstitution of beta-adrenergic receptor binding was typically 25-50% and could also be effected with soybean phosphatidylcholine in the presence of octyl glucoside. The reconstituted beta-adrenergic receptors were then fused with Xenopus laevis erythrocytes, which contain prostaglandin E1-sensitive adenylate cyclase [ATP pyrophosphate-lyase (cyclizing), EC 4.6.1.1] but few beta-adrenergic receptors and little or no catecholamine-sensitive adenylate cyclase. Fusion of reconstituted receptor with Xenopus laevis erythrocytes establishes a substantial (2- to 10-fold) stimulation of the hybrid adenylate cyclase by the beta-agonist isoproterenol. The extent of stimulation depends on the amount of reconstituted beta-adrenergic receptor added, is blocked by propranolol, and is eliminated by boiling the beta-adrenergic receptor prior to reconstitution. The successful coupling of a purified receptor to a heterologous adenylate cyclase opens the way to the study of receptor structure---function relationships.